117k views
0 votes
Y = (x + 1)(x − 1)(x − 3)

1 Answer

1 vote

Answer:


\huge\colorbox{violet}{✏﹏ \: ᶛɲƧཡэʀ \: }

y = (x + 1) (x - 1) (x - 3)

Use the distributive property to multiply x+1 by x-1 and combine like terms.

y = (x² - 1) (x - 3)

Use the distributive property to multiply x² - 1 by x - 3.

y = x³ - 3x² - x + 3.

ʰᵒᵖᵉ ⁱᵗ ʰᵉˡᵖˢ


\huge\blue{ \mid{ \underline{ \overline{ \tt ꧁❣ ʀᴀɪɴʙᴏᴡˢᵃˡᵗ2²2² ࿐ }} \mid}}

User Technupe
by
4.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.